Expression of symptoms elicited by a hammerhead viroid through RNA silencing is related to population bottlenecks in the infected host - Serra, P.; Navarro, B.; Forment, J.; Gisel, A.; Gago-Zachert, S.; Serio, F. di; Flores, R. (Wiley, 2023)
Chlorosis is frequently incited by viroids, small nonprotein-coding, circular RNAs replicating in nuclei (family Pospiviroidae) or chloroplasts (family Avsunviroidae). Here, we investigated how chrysanthemum chlorotic mottle viroid (CChMVd, Avsunviroidae) colonizes, evolves and initiates disease. Progeny variants of natural and mutated CChMVd sequence variants inoculated in chrysanthemum plants were characterized, and plant responses were assessed by molecular assays. We showed that: chlorotic mottle induced by CChMVd reflects the spatial distribution and evolutionary behaviour in the infected host of pathogenic (containing a UUUC tetranucleotide) and nonpathogenic (lacking such a pathogenic determinant) variants; and RNA silencing is involved in the initiation of the chlorosis in symptomatic leaf sectors through a viroid derived small RNA containing the pathogenic determinant that directs AGO1-mediated cleavage of the mRNA encoding the chloroplastic transketolase. This study provides the first evidence that colonization of leaf tissues by CChMVd is characterized by segregating variant populations differing in pathogenicity and with the ability to colonize leaf sectors (bottlenecks) and exclude other variants (superinfection exclusion). Importantly, no specific pathogenic viroid variants were found in the chlorotic spots caused by chrysanthemum stunt viroid (Pospiviroidae), thus establishing a clear distinction on how members of the two viroid families trigger chlorosis in the same host.